Repair Work Ethnographies Revisiting Breakdown, Relocating Materiality - Strebel, Ignaz; Bovet, Alain; Sormani, Philippe; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This pioneering book homes in on repair as an everyday practice. Bringing together exemplary ethnographies of repair work around the world, it examines the politics of repair, its work settings and intricate networks, in and across a wide range of situations, lay and professional. The book evidences the topical relevance of situated inquiry into breakdown, repair, and maintenance for engaging with the contemporary world more broadly. Airplanes and artworks, bicycles and buildings, cars and computers, medical devices and mobile phones, as virtually any commodity, infrastructure or technical artifact, have in common their occasional breakdown, if not inbuilt obsolescence. Hence the point and purpose of closely examining how and when they are fixed.
Introduction -- Chapter 1 / When Things Break Down -- Part I: Settings -- Chapter 2 / Repair Work as Inquiry and Improvisation: the Curious Case of Medical Practice -- Chapter 3 / 'A Good Enough Fix': Repair and Maintenance in Librarians' Digitization Practice -- Chapter 4 / Job Done: What Repair Does to Caretakers, Tenants and their Flats -- Part II: Networks -- Chapter 5 / Mobile Phone Repair Knowledges in Downtown Kampala: Local and Trans-local Circulations -- Chapter 6 / The Dance of Maintenance and the Dynamics of Urban Assemblages: The Daily (Re)assemblage of Paris Subway Signs -- Chapter 7 / Inquiring and experimenting with Urban Ecology: Pragmatist Lessons from Public Bicycle Repair -- Chapter 8 / Interruptions, Lunch Talks, and Support Circles: An Ethnography of Collective Repair in Steam Locomotive Restoration -- Part III: Politics -- Chapter 9 / Negotiating Repair: The Infrastructural Contexts of Practice and Power -- Chapter 10 / Inside the Bicycle: Repair Knowledge for All -- Chapter11 / Repair for the Masses? Gender and Care Work in the Fixers' Collective -- Afterword -- Chapter 12 / Repair as Transition: Time, Materiality, and Hope.
Keywords: Ethnology; Human geography; Sociology; Sociocultural Anthropology; Human Geography; Sociology